Influence of fast-track programs on patient-reported outcomes in total hip and knee replacement (THR/TKR) at Swedish hospitals 2011–2015: an observational study including 51,169 THR and 8,393 TKR operations - Berg, Urban; Dahl, Annette W-; Rolfson , Ola; Nauclér, Emma; Sundberg, Martin; Nilsdotter, Anna (Acta Orthopaedica, 2020)
Background and purpose — Fast-track care programs have been broadly introduced at Swedish hospitals in elective total hip and knee replacement (THR/TKR). We studied the influence of fast-track programs on patient-reported outcomes (PROs) 1 year after surgery, by exploring outcome measures registered in the Swedish arthroplasty registers. Patients and methods — Data were obtained from the Swedish Knee and Hip Arthroplasty Registers and included TKR and THR operations 2011–2015 on patients with osteoarthritis. Based on questionnaires concerning the clinical pathway and care programs at Swedish hospitals, the patients were divided in 2 groups depending on whether they had been operated in a fast-track program or not. PROs of the fast-track group were compared with not fast-track using regression analysis. EQ-5D, EQ VAS, Pain VAS, and Satisfaction VAS were analyzed for both THR and TKR operations. The PROMs for TKR also included KOOS. Results — The differences of EQ-5D, EQ VAS, Pain VAS, and Satisfaction VAS 1 year after surgery were small but all in favor of fast-track for both THR and TKR, also in subscales of KOOS for TKR except KOOS QoL. However, the effect sizes as measured by Cohens’ d formula were < 0.2 for all PROs, in both THR and TKR. Interpretation — Our results indicate that the fast-track programs may be at least as good as conventional care from the perspective of PROs 1-year postoperatively.